2002
DOI: 10.1108/13612020210441355
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the retail approach‐avoidance behavior of older apparel consumers

Abstract: The purpose of this research was to examine the four aspects of approach‐avoidance behavior (physical, exploratory, communication, performance and satisfaction) of older apparel consumers (those aged 65 and over). This research also examined the differences in age and shopping orientations relative to the importance of retail store attributes. Participants were 208 older consumers residing in the Southeastern part of the USA. Survey results revealed that older consumers preferred to shop department stores and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…Shopping orientation groups differed with regard to the importance placed on store attributes (Moye & Giddings, 2002). These results were confirmed in a study by Kim and Chen Yu (2005).…”
Section: Consumer Characteristics and Profilingsupporting
confidence: 56%
See 1 more Smart Citation
“…Shopping orientation groups differed with regard to the importance placed on store attributes (Moye & Giddings, 2002). These results were confirmed in a study by Kim and Chen Yu (2005).…”
Section: Consumer Characteristics and Profilingsupporting
confidence: 56%
“…Based on the findings that store image attributes, used by Canadian and English respondents as store selection criteria, were similar in ranking, Van de Velde et al (1996) concluded that similar clothing value hierarchies exist amongst different cultural groups sharing a root culture. Moye and Giddings (2002) found no differences between the age of older consumers (65 and older) and the importance of store attributes.…”
Section: Consumer Characteristics and Profilingmentioning
confidence: 67%
“…Results from studies on the relationship between demographic variables (age, gender, level of education, occupation, residence, income level, marital status and number of children) and perceived store image were marked by contradicting findings (Chowdhary, 1999;Gehrt & Yan, 2004;Hyllegard, Eckman, Descals & Borja, 2005;Moye & Giddings, 2002;Oates, Shufeldt & Vaught, 1996;Odekerken-Schröder, De Wulf, Kasper, Kleijnen, Hoekstra & Commandeur, 2001;Paulins & Geistfeld, 2003;Williams & Slama, 1995). Consequently no definitive conclusions can be drawn about the influence of demographic variables on the perceived importance of store image.…”
Section: Store Image Domain Specificationmentioning
confidence: 72%
“…The relationship between shopping orientation and store image perception was more conclusive although the shopping orientation groups that were identified in specific studies differed (Morschett, Swoboda & Foscht, 2005;Moye & Giddings, 2002;Moye & Kincade, 2002;Shim & Kotsiopulos, 1992;Visser & Du Preez, 2001). The results of Shim and Kotsiopulos (1992) indicated that shopping orientations predict the importance of store attributes.…”
mentioning
confidence: 99%
See 1 more Smart Citation